Identification of the necessary conditions for the success of manufacturers servitization - Matusek, Mirosław (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
The purpose of this paper is to employ a necessary condition analysis (NCA) approach to investigate the level of necessity of two conditions, separate organization for services and interfirm collaboration for service business performance depending on the type of adopted service orientation (services in support of the product (SSP) and services in support of the client’s actions business orientation (SSC). Servitization is now becoming an important factor favorable to manufacturers competitiveness. The adoption of service orientation and adequate service strategies includes building up an ability to deliver services and also, according to contingency theory, it requires changes in structure of organization. Unfortunately, it is not clear whether manufacturers should create a separate organization for services or if they should pursue an integration of the service organization into its corresponding product base strategic business unit. Empirical evidence and theoretical contributions can be found to support both sides of the argument. Moreover, some of the findings are inconsistent and even contrary to each other. Using a survey data set collected from a sample of 186 Polish manufacturers, this study explored the levels of necessity of the components by NCA. The research revealed that neither in case of SSP BO nor SSC BO separation of organization for services is not necessary condition to achieve both low and high level of service business performance. Also, the results show that different levels of service business performance require different threshold levels of inter-collaboration. This condition is more necessary when firms are SSC oriented.